Densidades de semeadura da gliricídia, em consorciação com o milho, no controle das plantas daninhas - Oliveira, Antônia Kênnia de (Universidade Federal Rural do Semi-Árido, 2016)
Weeds reduce corn yield and contribute to the incidence of pathogens and pests in the crop. They also can hinder the cultivation, including harvesting. There is interest in control methods of weeds that reduce environmental degradation and the weeding cost. The aim of this study was to determine the effects of seeding rate of Gliricídia (Gliricidia sepium) on weed control and corn yields. The experimental design was a randomized complete block design with split-plots and five replications. Cultivars 30F35H and 30F35YH, applied to the plots, were submitted to the following treatments: without hoeing; two hoeings (at 20 and 40 days after sowing) and intercropping with Gliricídia (20, 40, 60 and 80 viable seeds m-²). In intercropping, gliricidia was sown by broadcasting on the occasion of corn sowing grass among the rows. The cultivars were compared by Tukey test and Dunnett's test was used to compare the methods of weed control, using treatment two heings as a control. The planting densities, along with the "absence of hoeing" ("zero density" planting gliricidia), were also compared through regression analysis. Two hoeing reduced weeds growth, compared to other control methods, besides providing greater economic return. In the intercroppings, the best yields of green and dry corn were obtained planting gliricídia among densities of 20 and 40 seeds m-2. The hybrids did not differ as to green corn yields and grain yield
Density of gliricidia sowing, intercropped with corn, on the weeds’ control
Keywords: Plantas daninhas; Milho; Gliricidia sepium; Weeds; Zea mays; Gliricídia sepium; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA